Financial literacy, gender, and economic behavior: The perspective of undergraduate accounting students - Setiana, Sinta; Debbianita, Debiannita; Eunike, Eiren (LPMP Imperium, 2023)
This study aims to check and analyze the impact of financial literacy and gender on economic behavior. The population comprises 247 active undergraduate accounting students of Maranatha Christian University in batches 2019, 2020, and 2021. Moreover, the Slovin formula with a 1% error margin calculates the total samples 241, taken by stratified random sampling. Unfortunately, only 229 students responded to the survey between September and October 2022. Therefore, the structural equation based on covariance analyzes the related responses through checking hypotheses. After testing and discussing them, this study infers that financial literacy does not affect economic behavior. However, males are better at financial behavior than females. Public interest statementsBased on the result of this study, the undergraduate accounting department suggests that the students follow a registered financial planning class before graduation to get the recognized competency documented in the diploma supplement. Coincidentally, the class to get this certification is organized by appointed lecturers in the undergraduate management department at Maranatha Christian University. Therefore, this class can give them a deeper understanding of personal financial management.